2013
DOI: 10.1186/1465-9921-14-121
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-inducible chemokines reflect severity and progression in sarcoidosis

Abstract: BackgroundIdentification of serum proteins that track with disease course in sarcoidosis may have clinical and pathologic importance. We previously identified up-regulated transcripts for interferon-inducible chemokines CXCL9, and CXCL10, in blood of sarcoidosis patients compared to controls. The objective of this study was to determine whether proteins encoded by these transcripts were elevated in serum and identified patients with remitting vs. chronic progressive sarcoidosis longitudinally.MethodsSerum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 41 publications
4
44
0
9
Order By: Relevance
“…CXCL9 is an IFN-cinducible chemokine that, upon binding to its receptor CXCR3, facilitates recruitment of T-cells to inflamed tissues in human autoimmune diseases. We and others have demonstrated elevations in CXCL9 protein levels in sarcoidosis sera [15,21], bronchoalveolar lavage (BAL) fluid [15,21,33] and granulomas [34]. We further show that CXCL9 gene expression inversely correlated with DLCO % predicted, independent of time from diagnosis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…CXCL9 is an IFN-cinducible chemokine that, upon binding to its receptor CXCR3, facilitates recruitment of T-cells to inflamed tissues in human autoimmune diseases. We and others have demonstrated elevations in CXCL9 protein levels in sarcoidosis sera [15,21], bronchoalveolar lavage (BAL) fluid [15,21,33] and granulomas [34]. We further show that CXCL9 gene expression inversely correlated with DLCO % predicted, independent of time from diagnosis.…”
Section: Discussionmentioning
confidence: 66%
“…Unexpectedly, the IFN-inducible chemokine CXCL9 gene (factor 7) was not intercorrelated with the other IFN-related genes in factor 1. We had particular interest in CXCL9 (factor 7), as CXCL9 is upregulated in gene network analyses of sarcoidosis organ tissues [19,20], and we and others have previously shown that serum protein levels of this chemokine are upregulated in sarcoidosis [15,21]. In summary, factor analysis of the qPCR results provided confirmation of the IFN, pattern recognition and TCR pathways in a separate replicate cohort, and additionally demonstrated a separate factor for CXCL9.…”
Section: Factor Analysis Demonstrates Distinct Clusters Of Intercorrementioning
confidence: 64%
See 1 more Smart Citation
“…The authors were able to demonstrate that patients with more severe disease expressed higher levels of tumor necrosis factor alpha (TNFα), and also had a greater response to infliximab [27]. Novel biomarkers, such as CXCL9, are likely to provide additional avenues for precision medicine in sarcoidosis treatment [28].…”
Section: Biological Agentsmentioning
confidence: 89%
“…86 SIL-2R is also elevated in sarcoidosis and has been extensively studied in the disease. 87,88 Su et al found that sIL-2R levels were elevated in sarcoidosis compared with healthy controls, although the sIL-2R levels did not correlate with lung disease severity. 87 The amount of sIL-2R does correlate, however, with eye inflammation in sarcoidosis patients.…”
Section: Sarcoidosismentioning
confidence: 99%